IMPROVING FAMILY ABILITIES THROUGH BONDRES DIABETIC EDUCATION MODEL: A QUASI-EXPERIMENTAL RESEARCH - I Dewa Ayu Rismayanti; Sundayana, I Made; Supriati, Lilik; Marthasari, Ni Ketut Putri (Indonesian Journal of Community Health Nursing, 2025)
Introduction: Families play an important role in the well-being and self-management of diabetes patients, but only 25% participate in diabetes programs, with only 27.6% of caregivers having self-management abilities for type 2 diabetes patients and 64.6% having low foot care abilities. This paper aimed to analyze the impact of the health education model through Bondres media on the ability of families to care for T2DM patients. Methods: This research employed a quasi-experimental design utilizing a cross-sectional study approach, and an intervention model of health education using Bondres media on family and patients with T2DM in Buleleng Regency. The sampling utilized the probability sampling method through cluster random sampling, resulting in a total of 106 respondents consisting of 53 interventions and 53 controls. The independent variable is the health education model using Bondres, while the dependent variable is family abilities. The data collection instrument used a questionnaire. This research data was analyzed using the Wilcoxon and Mann-Whitney statistical tests. Results: The results showed that the family’s abilities: healthy diet (p=0,0001), physical activity (p=0,0001), consuming medicine (p=0,0001), management of blood pressure (p=0,001), rest and stress (p=0,0001), and smoking habit (p=0,0001). Conclusion: The health education model using Bondres media significantly improved the family’s ability to provide care for patients with T2DM. This approach proved effective in enhancing knowledge and practices in DM management.